IN VITRO STUDY OF THE ANTHELMINTIC ACTION OF TRIGONELLA FOENUM GRAECUM L. GROWN IN IRAN - T.Ghafagaai; H. Farid; A.Pourafkari (Tehran University of Medical Sciences, 1980)
The water extract of Trigonella foenum graecum stem and leaves was tested for lethal activity against Hymenolepis nana, Syphacia obvelata, and Moniezia expansa. The plant extract demonstrated good anthelmintic activity in vitro which is directly related to the concentration of the extract used. The extract also prevents the formation of Ascaris larvae from the eggs of Ascaris lumbrico- ides (human). Department of Pharmacology and Department of Pathobiology, School of Medicine, Universety of Isfahan, Isfahan IRAN.